A tale of culture-bound regime evolution: the centennial democratic trend and its recent reversal. Issue 3 (3rd April 2019) - Brunkert, Lennart; Kruse, Stefan; Welzel, Christian
ABSTRACT: Using a new measure of "comprehensive democracy, " our analysis traces the global democratic trend over the last 116 years, from 1900 until 2016, looking in particular at the centennial trend's cultural zoning. As it turns out, democracy has been proceeding and continues to differentiate the world's nations in a strongly culture-bound manner: high levels of democracy remain a distinctive feature of nations in which emancipative values have grown strong over the generations. By the same token, backsliding and autocratization are limited to cultures with under-developed emancipative values. In line with this finding, public support for democracy neither favours democratization, nor does it prevent autocratization in disjunction from emancipative values. On the contrary, public support for democracy shows such pro-democratic effects if – and only if – it co-exists in close association with emancipative values. The reason is that – in disconnect from emancipative values – support for democracy frequently reverts its meaning, indicating the exact opposite of what intuition suggests: namely, support for autocracy. In conclusion, the prospects for democracy are bleak where emancipative values remain weak.